2015
DOI: 10.1038/srep11360
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale identification of encystment-related proteins and genes in Pseudourostyla cristata

Abstract: The transformation of a ciliate into cyst is an advance strategy against an adverse situation. However, the molecular mechanism for the encystation of free-living ciliates is poorly understood. A large-scale identification of the encystment-related proteins and genes in ciliate would provide us with deeper insights into the molecular mechanisms for the encystations of ciliate. We identified the encystment-related proteins and genes in Pseudourostyla cristata with shotgun LC-MS/MS and scale qRT-PCR, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…The pathway in the flagellate Giardia lamblia , for example, is well characterized, as cysts are a key virulence mechanism allowing it to survive in the environment and infect new hosts [ 102 , 160 , 161 , 162 ]. The encystment process is also well studied in ciliates [ 163 , 164 , 165 , 166 ].…”
Section: Future Prospectsmentioning
confidence: 99%
“…The pathway in the flagellate Giardia lamblia , for example, is well characterized, as cysts are a key virulence mechanism allowing it to survive in the environment and infect new hosts [ 102 , 160 , 161 , 162 ]. The encystment process is also well studied in ciliates [ 163 , 164 , 165 , 166 ].…”
Section: Future Prospectsmentioning
confidence: 99%
“…During transformation of the trophonts into cysts, the cell morphology changes sharply accompanied by the rapid modifications in intracellular proteins 13,14 . Therefore, dramatic changes occurring in the proteins suggested an activation of the ubiquitin-proteasome system to meet the needs of protein degradation during cell morphological changes 8 . Our comparative transcriptomic data showed that the signaling pathway of the ubiquitin-mediated proteolysis was significantly upregulated in the cysts compared to the trophonts.…”
mentioning
confidence: 99%
“…Together, F-actin is required for both basal and starvation-induced autophagy in higher eukaryotes [22]. Therefore, F-actin upregulation could promote vegetative cell's shrinkage of P. cristata and enhanced the cell autophagy via regulating actin cytoskeleton, thereby promoting the formation of the dormant cysts [9]. CPT1 is a key enzyme for β-oxidation of fatty acid, and increased expression of CPT1 causes decomposition of fatty acids [23].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al identified that several proteins were associated with encystment of Euplotes encysticus including type II cytoskeletal 1, calpain-like protein, formate acetyltransferase, alpha S1 casein, and cold-shock protein by 2D electrophoresis and MALDI-TOF MS techniques [8]. Gao et al also identified proteins and genes in dormant cysts of P. cristata including fibrillarin-like rRNA methylase, ADP ribosylation factor, Rab12, and MAPK-related kinase by shotgun LC-MS/MS and scale quantitative real-time PCR (qRT-PCR) analysis [9]. Jiang et al found AMPK, CaMK, ABCC4, ERK1/2, and PP1 were associated with the cyst formation of Colpoda aspera through transcriptomic techniques [10].…”
Section: Introductionmentioning
confidence: 99%